Spindle black holes and theories of class F $$ \mathcal{F} $$ - Kiril Hristov; Minwoo Suh (Journal of High Energy Physics)
Abstract We construct solutions in the form of AdS 2 × Σ, where Σ denotes a spindle geometry, within a particular 4d N $$ \mathcal{N} $$ = 2 gauged supergravity with vector multiplets and a charged hypermultiplet stemming from a consistent truncation of 6d matter coupled F(4) gauged supergravity on a Riemann surface. We also compute the Bekenstein-Hawking entropy for the presumed asymptotically AdS 4 black hole solutions, providing a dual prediction for the spindle index of 3d superconformal field theories falling under the class F $$ \mathcal{F} $$ . Notably, the gravitational block description of the solutions accurately replicates the entropy and the values of scalar fields at the two orbifold points of the spindle, validating our findings.